Determinants of Private University Lecturer Engagement in Bekasi City, West Java, Indonesia - Junengsih, Junengsih; Yusnita, Nancy; Sunaryo, Widodo (Eastasouth Institute, 2024)
This research aims to find ways to increase lecturer engagement through transformational leadership and personality variables. The sample for this research was lecturers at private universities in the city of Bekasi, totaling 166 lecturers. The method used is path analysis and indicator analysis techniques. This research concludes that; 1) Strengthening Transformational Leadership can increase the engagement of permanent lecturers at private universities. 2) Strengthening Personality can increase the engagement of permanent lecturers at private universities. Suggestions, to strengthen transformational leadership and personality, you can strengthen the indicators for these variables.